Design of Battery Thermal Management System with Considering the Longitudinal and Transverse Temperature Difference - Junhao Dong; Xipo Lu; Yang Sun; Vladislav Mitin; Huaping Xu; Wei Kong (Energies, 2022)
For a bottom-liquid-cooled battery thermal management system (BTMS), the small contact area between the battery bottom and the cold plate leads to a large temperature difference in the battery height direction. In addition, the increase in coolant temperature from the inlet to the outlet results in an excessive temperature difference in the battery module in the coolant flow direction. In order to solve the above issues, a wavy channel was first designed to strengthen the heat exchange between the battery bottom and the cold plate. The maximum battery module temperature for the wavy-channel design is 29.61 °C, which is a reduction of 1.75 °C compared to the straight-channel design. Then, the transverse temperature difference in the battery module was reduced by introducing a composite-channel design. Finally, on the basis of the composite channel, phase change material (PCM) was added to the battery’s top surface to reduce the temperature difference in the battery height direction. The results show that the maximum temperature and maximum temperature difference in the battery module of the composite-channel/PCM design proposed in this study are reduced by 6.8% and 41%, respectively, compared with the conventional straight-channel design.